Imagery of Intrinsic Elements Found in Edgar Allan Poe’s Poetry - Fitriyah, Fitriyah; Ghozali, Imam; Wardhani, Ika Desy (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2022)
This research was purposed to found and explained the kinds of imagery in three poetries by Edgar Allan Poe. All of content poetry is true story of Edgar Allan Poe’s life. The poetry that was taken by researchers are “To My Mother, Serenade, and Spirits of the Dead”. The researcher analyzed seven types of imagery as follows: visual imagery, auditory imagery, olfactory imagery, gustatory imagery, tactile imagery, organic imagery, and kinesthetic imagery. The method was regarded qualitative as research design. The researcher used documentation technique in collecting the data. Analysis data in this research implied content analysis approach. The result of this research showed forty-seven imageries in the three poetries of Edgar Allan Poe. The imagery found as follows;23 visual, 4 auditory, 2 olfactory, 2 tactile, and 16 organics. The researcher found five types of imagery in three poetries, but the visual imagery is very dominant raised of each poetry.